Working effectively with patients with comorbid mental illness and substance abuse: a case study using a structured motivational behavioural approach - Lawn, Sharon (BMJ Publishing Group, 2009)
This case describes the use of innovative person-centred motivational behaviour change tools to enhance chronic condition self-management with a person with chronic paranoid schizophrenia, significant drug abuse and multiple psychosocial issues. In standard care, the complexity of this patient’s presentation, their cognitive impairment level and history of violence would likely exclude them from many therapies and treatment programs as unsuitable or in the “too hard” basket. In fact, using a motivational and highly person-centred approach proved to be extremely necessary and rewarding for the person and their mental health worker. This approach provided a clear structure, actual tools and a clear rationale for what many would argue, yet is often ill-defined, was “just good clinical practice”. However, it also facilitated the development of “something special” in the relationship between the person and their worker that is central to person-centred care. Through a semistructured, motivational, sequential process that encouraged gradual disclosure and greater self-awareness by the client and active listening by the worker, greater collaboration and shared responsibility was enhanced.